Adapting a behavioral coaching framework for mental toughness development. Issue 1 (2nd January 2018) - Anthony, David R.; Gordon, Sandy; Gucciardi, Daniel F.; Dawson, Brian
ABSTRACT: Mental Toughness (MT) development is an important consideration when seeking to increase and maintain high levels of performance in sport settings. There has been limited research on effective methods to develop MT, and an opportunity exists to incorporate other developmental frameworks in psychology that have shown a positive effect on performance. In this article, we detail a coach-targeted education program aimed at increasing the frequency of desirable mentally tough behaviors (MTb) in elite athletes, which draws on recent work on MTb and an established behavioral coaching model (i.e., GROW) as the guiding framework. The theoretical foundations of behavioral coaching and relationship with improving performance are briefly discussed. We then describe how we applied the behavioral coaching model in a professional team sport environment during the course of a competitive season, including learning points and future considerations for those practitioners looking to develop MT in sporting contexts.